Collision dynamics of H+ + N2 at low energies based on time-dependent density-functional theory. (16th January 2018) - Yu, W; Zhang, Y; Zhang, F S; Hutton, R; Zou, Y; Gao, C-Z; Wei, B
Abstract: Using time-dependent density-functional theory at the level of local density approximation augmented by a self-interaction correction and coupled non-adiabatically to molecular dynamics, we study, from a theoretical perspective, scattering dynamics of the proton in collisions with the N2 molecule at 30 eV. Nine different collision configurations are employed to analyze the proton energy loss spectra, electron depletion, scattering angles and self-interaction effects. Our results agree qualitatively with the experimental data and previous theoretical calculations. The discrepancies are ascribed to the limitation of the theoretical models in use. We find that self-interaction effects can significantly influence the electron capture and the excited diatomic vibrational motion, which is in consistent with other calculations. In addition, it is found that the molecular structure can be readily retrieved from the proton energy loss spectra due to a significant momentum transfer in head-on collisions.